Pelatihan Bermain pada Pengasuh dapat Meningkatkan Pengetahuan, Sikap dan Keterampilan Pengasuhan - Eka Oktavianto; Alfi’atul Mubasyiroh (STIKes Surya Global Yogyakarta, 2017)
Background: Childcare problems will have an impact on growth and development. Currently there are many caregivers who do not understand how to take care of children. Many of them do not know the importance of playing and interacting with children yet. Therefore it is important to provide training to them.Objective: Studywas aimed to evaluate the effect of play training in caregiver on knowledge, affective, and skill of caregiver at LKMD Singosaren kindergarten Banguntapan Bantul Yogyakarta. Methods: Pre-experimental with one group pre and post-test design without control was applied in this study. Nineteen pairs of caregiver and preschool children were selected by using purposive sampling. Data was collected by using questionnaires and observation form. Then, data analysis was performing by dependent sample t test. Result: This study found that knowledge was increasing about 3,68 after the training is given to the respondents. The affective was increasing about 5 after the training is given to the respondents. The skill was increasing about 32 after the training is given to the respondents Comparative test between pre-test toward post-test I and II showed that p=0,000 (p value 0,05).Conclution: Providing the play training has found significantly affect on knowledge, affective, and skill of caregiver to provide better caring in preschool children.